2006
DOI: 10.1159/000095741
|View full text |Cite
|
Sign up to set email alerts
|

Association of a Functional Polymorphism in the Serotonin Transporter Gene with Personality Traits in Females in a Polish Population

Abstract: The aim of our study was to determine whether the 5-HTTLPR polymorphism is related to temperamental traits measured using the Formal Characteristics of Behavior – Temperament Inventory (FCB-TI) and personality traits assessed by the NEO Five-Factor Inventory (NEO-FFI) questionnaire. The sample comprised 200 unrelated females, aged 18–29 years. DNA of the subjects was isolated from buccal epithelial cells, and 5-HTTLPR polymorphism was genotyped using PCR. The subjects were divided into SS, SL and LL groups acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Moreover, recent literature suggests that the 5HTTLPR genotype may have opposite effects on behavioral characteristics in men and women (Brummett et al 2008c;Dragan and Oniszczenko 2006;Du et al 2000;Sjoberg et al 2006;Walderhaug et al 2007). A previous study by our group found that girls with the short allele who were exposed to traumatic conflict within the family had the highest risk of depression, whereas boys with the long allele who were exposed to the psychosocial risk of living in multi-family houses and with separated parents had the highest risk of depression .…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, recent literature suggests that the 5HTTLPR genotype may have opposite effects on behavioral characteristics in men and women (Brummett et al 2008c;Dragan and Oniszczenko 2006;Du et al 2000;Sjoberg et al 2006;Walderhaug et al 2007). A previous study by our group found that girls with the short allele who were exposed to traumatic conflict within the family had the highest risk of depression, whereas boys with the long allele who were exposed to the psychosocial risk of living in multi-family houses and with separated parents had the highest risk of depression .…”
Section: Introductionmentioning
confidence: 75%
“…Moreover, the 5HTTLPR genotype has different implications for personality traits and emotional well-being depending on sex (Brummett et al 2008c;Dragan and Oniszczenko 2006;Walderhaug et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…Of these, data were unavailable on k = 9 study samples (Bachner-Melman et al 2005; Cohen et al 2002; Kim et al 2005; Kim et al 2006a; Kremer et al 2005; Lerman et al 2000; Park et al 2004; Schmidt et al 2000; Thierry et al 2004), so that a total of 42 studies, comprising k = 55 study samples, contributed to the meta-analysis (Ball et al 1997; Benjamin et al 2000a; Brummett et al 2003; Comings et al 2000; Cruz et al 1995; Deary et al 1999; Dragan and Oniszczenko 2006; Du et al 2000; Ebstein et al 1997; Flory et al 1999; Greenberg et al 2000; Ham et al 2004; Hamer et al 1999; Hariri et al 2005; Herbst et al 2000; Hu et al 2000; Jacob et al 2004; Joo et al 2007; Jorm et al 1998; Katsuragi et al 1999; Kumakiri et al 1999; Lang et al 2004; Lanzagorta et al 2006; Lesch et al 1996; Mazzanti et al 1998; Middeldorp et al 2007; Monteleone et al 2006; Munafo et al 2006; Nakamura et al 1997; Nilsson et al 2007; Osher et al 2000; Ricketts et al 1998; Samochowiec et al 2001; Samochowiec et al 2004; Schmitz et al 2007; Sen et al 2004b; Stein et al 2007; Strobel et al 2000; Szekely et al 2004; Tsai et al 2002; Umekage et al 2003; Vormfelde et al 2006; Willis-Owen et al 2005). This included 7 studies, comprising k = 15 study samples, that reported data on multiple personality instruments from the same sample (Jacob et al 2004; Kumakiri et al 1999; Nakamura et al 1997; Osher et al 2000; Samochowiec et al 2004; Vormfelde et al 2006; Willis-Owen et al 2005), and 3 studies, comprising k = 5 study samples, that recruited participants based on a selected personality score (Ball et al 1997; Deary et al 1999; Willis-Owen et al 2005).…”
Section: Resultsmentioning
confidence: 99%
“…After the publication of this work other studies were published, two of which with positive results [24,25] and six of which with negative results [26][27][28][29][30][31]. Also children shyness, part of adult HA, has been associated with the short SERTPR variant [32].…”
Section: Harm Avoidancementioning
confidence: 89%